2016
DOI: 10.1007/s13197-015-2031-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin inhibits quorum signalling pathway of a food borne opportunistic pathogen

Abstract: Quorum sensing (QS) is the process of population dependent cell to cell communication used by bacteria to regulate their phenotypic characteristics. Key virulence factors that determine the bacterial pathogenicity and food spoilage were found to be regulated by QS mechanism. Hence, disrupting the QS signaling pathway could be an attractive strategy to manage food borne pathogens. In the current study, QS inhibitory activity of a naturally occurring anthocyanincyanidin and its anti-biofilm property were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Molecular docking methods and dynamics simulations have previously been combined to analyze the QS-inhibiting efficiency of screened compounds. For example, aspirin was shown to act as an anti-QS agent against P. aeruginosa by molecular docking studies57, and molecular docking and dynamics simulation studies were used to show that quercetin and cyanidin can act as competitive inhibitors for signaling molecules in the LasR receptor pathway5859.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking methods and dynamics simulations have previously been combined to analyze the QS-inhibiting efficiency of screened compounds. For example, aspirin was shown to act as an anti-QS agent against P. aeruginosa by molecular docking studies57, and molecular docking and dynamics simulation studies were used to show that quercetin and cyanidin can act as competitive inhibitors for signaling molecules in the LasR receptor pathway5859.…”
Section: Discussionmentioning
confidence: 99%
“…The light microscopic analysis method described for biofilm formation on a glass cover slip was performed as described previously. 36 Briefly, the C. violaceum (CV12472) isolate was added to the fresh LB medium (supplemented with 0.2% (w/v) glucose) containing glass cover slips using a 6-well flat bottom microtitre plate with EA fruit extracts and along with appropriate control wells without the extracts. The plate was incubated in a static condition at 30 °C for 24 h. After incubation, the unbound planktonic cells from both treated and untreated glass cover slips were removed, rinsed with sterile distilled water, and stained with 0.2% crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…Gopu and Shetty reported that the naturally occurring anthocyanin-cyanidin significantly inhibited QS-dependent phenotypes such as biofilm formation (72.43%), violacein production (73.96%), and EPS production (68.65%) in the opportunistic pathogen Klebsiella pneumoniae in a concentration-dependent manner. [ 47 ] Rosmarinic acid extracted from sweet basil bound to the QS-regulator RhlR of P. aeruginosa PAO1 and competed with the bacterial ligand N -butanoyl-homoserine lactone (C4-HSL). Furthermore, it stimulated a greater increase in RhlR-mediated transcription in vitro than that of C4-HSL.…”
Section: P Hytochemicals As Q Uorum mentioning
confidence: 99%